PERANCANGAN INTERIOR GEDUNG AUDITORIUM RRI DENPASAR, BALI (Jurnal iSpectrum, 2023)
Along with the development of time and the population causes the development of a variety of activities in the community. In line with the many activities and activities that develop in the community, it is also balanced with the increasingly complex needs of the community as a result of these many activities. One of the important needs to be fulfilled is the existence of a space where the community can carry out these various activities. The space is a multipurpose building or auditorium building which can accommodate many people in one place and at the same time facilitate the activities that take place in it.In the city of Denpasar, there are many multipurpose buildings, one of which is the RRI Denpasar Auditorium. However, along with the times, this building began to be forgotten and less attractive to the public even though it has a strategic location because it is in the middle of the city. Not only that, the facilities inside are also outdated so they don't meet the current auditorium building standards.Through an interior approach based on observations and related literature studies, the RRI Denpasar Auditorium building will be redesigned or redesigned to meet the needs and desires of the community so that they can exist again in the community. In addition, with the theme approach of the Neo-Yankee's Herboren concept, this building will be revived by bringing the history and values engraved in it and will be brought back in a more modern and more flexible form for today's society.